MENINGKATKAN MINAT BELAJAR ANAK MELALUI STRATEGI INDEX CARD MATCH (ICM) PADA ANAK USIA 5-6 TAHUN DI TK AL-KHOLIDIYAH SEDINGINAN KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Fitri Nanda; Wusono Indarto; Hukmi Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to determine how high the increased interest in studying children aged 5-6 years in kindergarten Al-Kholidiyah Sedinginan subdistrict Tanah Putih Regency Rokan Hilir using strategy Index Card Match (ICM). This research is a classroom action research conducted in 2. Data collection tool used in this study is in the form of sheets. The number of samples in this study were 14 children consisting of 8 boys and 6 children girls. Based on the analysis of the assessment process there was an increase of 2 cycles. The result of this research are very satisfying because getting the average value is very significant from before action to cycle I and cycle I to cycle II, that is from the average value 40,63 increased to 55,36 by percentage 36,25%, and from 55,36 increased 80,06 by percentage 44,61%. From the results of these studies concluded that the strategy Index Card Match (ICM) to learning by giving a positive response to children and able to increase interest in learning in children.Key Words: Interest in learning, strategy Index Card Match (ICM)